Impact of factories on school-going children: a case study on Hatiaba village in Gazipur district - Patwary, Md. Monirul Islam (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2022.